2004
DOI: 10.1007/s00442-004-1540-4
|View full text |Cite
|
Sign up to set email alerts
|

Feedback interactions between needle litter decomposition and rhizosphere activity

Abstract: The aim of our study was to identify interactions between the decomposition of aboveground litter and rhizosphere activity. The experimental approach combined the placement of labelled litter (delta13C=-37.9 per thousand ) with forest girdling in a 35-year-old Norway spruce stand, resulting in four different treatment combinations: GL (girdled, litter), GNL (girdled, no litter), NGL (not girdled, litter), and NGNL (not girdled, no litter). Monthly sampling of soil CO2 efflux and delta13C of soil respired CO2 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
168
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(189 citation statements)
references
References 35 publications
18
168
0
3
Order By: Relevance
“…Priming is almost ubiquitously observed in ecosystem studies where organic matter inputs are altered in laboratory incubations (reviewed by Blagodatskaya and Kuzyakov, 2008) or directly on the field (Boone et al, 1998;Borken and Muhs, 2002;Chemidlin-Prévost-Bouré et al, 2010;Subke et al, 2004;Sulzman et al, 2005;Xiao et al, 2015). Priming can occasionally be negative but most commonly has a stimulative effect on the decomposition of organic matter that decomposes.…”
Section: B Guenet Et Al: Priming Effect In Global Land Biosphere Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Priming is almost ubiquitously observed in ecosystem studies where organic matter inputs are altered in laboratory incubations (reviewed by Blagodatskaya and Kuzyakov, 2008) or directly on the field (Boone et al, 1998;Borken and Muhs, 2002;Chemidlin-Prévost-Bouré et al, 2010;Subke et al, 2004;Sulzman et al, 2005;Xiao et al, 2015). Priming can occasionally be negative but most commonly has a stimulative effect on the decomposition of organic matter that decomposes.…”
Section: B Guenet Et Al: Priming Effect In Global Land Biosphere Modelmentioning
confidence: 99%
“…A second evaluation of the ORCHIDEE-PRIM model was performed at ecosystem scale against observations of four litter manipulation experiments (Boone et al, 1998;Chemidlin-Prévost-Bouré et al, 2010;Subke et al, 2004;Sulzman et al, 2005) and one compost amendment experiment (Borken and Muhs, 2002). In the litter experiments, two treatments and a control are generally performed.…”
Section: Ecosystem-level Data Used For Evaluation Of the Priming Modelmentioning
confidence: 99%
“…Among others, Boone et al [6] reported a higher Q 10 for rhizosphere respiration (4.6) than for soil respiration excluding roots (2.5); however, the higher Q 10 for rhizosphere respiration most likely results from the multiplicative effects of several processes: enzyme activity, root growth and photosynthate production. On another hand, Subke et al [42] showed that rhizosphere activity increases litter respiration, possibly by simulating microbial activity through the addition of easily accessible carbon (soil priming).…”
Section: Temperature Effectmentioning
confidence: 99%
“…Previous long-term studies of the effects of root disruption (Siira-Pietikäinen et al, 2001;Brant et al, 2006) or tree girdling (Högberg and Högberg, 2002;Subke et al, 2004) have all found marked decreases in fungal biomass, because of detrimental effects on mycorrhizal taxa (Yarwood et al, 2009). Physical disturbance of the microbial community in boreal forest soils also frequently results in release of NH 4 þ (Yavitt and Fahey, 1984;Siira-Pietikäinen et al, 2001;Lavoie and Bradley, 2003;Piirainen et al, 2007), and elevated NH 4 þ levels have also been observed in association with repeated freeze-thaw cycles (Sulkava and Huhta, 2003) and clear-cutting (Carmosini et al, 2003;Lapointe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%